Editorial: Redox Potential and Metabolic Behavior in Gastrointestinal Cancers - Biagioni, Alessio; Peri, Sara; Schiavone, Nicola; Giommoni, Elisa; Papucci, Laura (Frontiers in Oncology, 2022)
Gastrointestinal cancers refer to a large and heterogeneous family of malignancies localized in the esophagus, stomach, liver, pancreas, small and large intestine, rectum and anus that account for over 5,000,000 new cases per year and about 3,540,000 deaths worldwide (1). Characterized by very different diffusion between Eastern and Western countries, several factors influence the epidemiological distribution including environmental risk factors, prevention strategies and lifestyles. However, these histotypes of cancers are now widely recognized as very heterogeneous tumors (2), increasing the difficulty to find appropriate and efficient treatment regimens (3). One of the recently updated Hanahan’s hallmarks of cancer (4) is represented by dysregulation in cellular energetics and metabolism. This aspect was initially hinted at by the well-known Warburg effect for which hyper-proliferating cells showed accelerated conversion of glucose to lactate even in the presence of abundant oxygen in order to sustain energetics demand (5). This generates an abundant lactate secretion leading to rapid extracellular acidification which might often pair with an increased tumor migration, invasion, vascularization, chemoresistance and in the last metastasization (6) whilst the typical mitochondrial oxidative metabolism is inhibited also due to severely damaged mitochondria (7). This concept evolved in time not only for glucose metabolism, indeed alterations in several biochemical pathways have been shown, and cancer-associated lipid metabolism is to date an element of debate (8).